Education and Character Development in the Sundanese Manuscript Texts Pupujian and Nadoman in the Millennial Era - Elis Suryani Nani Sumarlina; Rangga Saptya Mohamad Permana; Undang Ahmad Darsa (Jurnal IKADBUDI, 2025)
Collecting, describing, transliterating, editing, and studying the Pupujian texts derived from Sundanese manuscripts, codified at Islamic boarding schools, is a challenging endeavor. The contents are religious/Islamic, representing cultural assets derived from the ingenuity of Sundanese forebears, whose presence in the contemporary millennial era is hardly acknowledged in madrasas, mosques, prayer rooms, or Islamic boarding schools. If neglected and unpreserved, it will be lost to history. The examination of Character Education in Sundanese manuscript texts is conducted from a literary and cultural standpoint, focusing on the elements that shape the character of the nation's youth, encompassing discipline, responsibility, heroism, faith, Islamic teachings, prophetic history, Islamology, and the relationships between humans and God, among humans, and with the environment. Utilized descriptive comparative analysis, philological methodologies, codicology, textology, and hermeneutic studies of literary and cultural works to serve as a literacy reference for other disciplines in the contemporary millennial age. The Pupujian manuscript is intricately connected to the 'yellow book,' which is significantly linked to the development of the nation's character and identity.